Diagnostic value of eosinopenia and neutrophil to lymphocyte ratio on early onset neonatal sepsis - Rocky Wilar (Korean Pediatric Society, 2019)
Purpose To determine the diagnostic value of eosinopenia and the neutrophil-to-lymphocyte ratio (NLR) in the diagnosis of early onset neonatal sepsis (EONS). Methods This cross-sectional study was conducted in the Neonatology Ward of R.D. Kandou General Hospital Manado between July and October 2017. Samples were obtained from all neonates meeting the inclusion criteria for EONS. Data were encoded using logistic regression analysis, the point-biserial correlation coefficient, chi-square test, and receiver operating characteristic curve analysis, with a P value <0.05 considered significant. Results Of 120 neonates who met the inclusion criteria, 73 (60.8%) were males and 47 (39.2%) were females. Ninety (75%) were included in the sepsis group and 30 (25%) in the nonsepsis group. The mean eosinophil count in EONS and non-EONS groups was 169.8±197.1 cells/mm3 and 405.7±288.9 cells/mm3 , respectively, with statistically significant difference (P<0.001). The diagnostic value of eosinopenia in the EONS group (cutoff point: 140 cells/mm3 ) showed 60.0% sensitivity and 90.0% specificity. The mean NLR in EONS and non-EONS groups was 2.82±2.29 and 0.82±0.32, respectively, with statistically significant difference (P<0.001). The diagnostic value of NLR in the EONS group (cutoff point, 1.24) showed 83.3% sensitivity and 93.3% specificity. Conclusion Eosinopenia has high specificity as a diagnostic marker for EONS and an increased NLR has high sensitivity and specificity as a diagnostic marker for EONS.